Enriching educational products: Islamic private institutions of higher learning in Malaysia. - Shuib, Munir (National Higher Education Research Institute, Universiti Sains Malaysia, 2005)

(untitled)
Islamic Private Institutions of Higher Learning (IPIHLs) are a new type of educational institution in Malaysia. Together with other institutions of higher learning, IPIHLs aim to establish Malaysia as an international hub for higher education. However, unlike other institutions of higher learning in the Malaysian educational system, IPIHLs have very definite and different philosophy, objectives and modus operandi.